Cyclophosphamide‐based hematopoietic stem cell mobilization before autologous stem cell transplantation in newly diagnosed multiple myeloma. Issue 3 (8th October 2014) - Tuchman, Sascha A; Bacon, Wendi A; Huang, Li‐Wen; Long, Gwynn; Rizzieri, David; Horwitz, Mitchell; Chute, John P.; Sullivan, Keith; Morris Engemann, Ashley; Yopp, Amanda; Li, Zhiguo; Corbet, Kelly; et al.
Abstract : High‐dose cyclophosphamide (Cy) is frequently employed for peripheral blood mobilization of hematopoietic stem cells before high‐dose chemotherapy with autologous stem cell transplantation (ASCT) in multiple myeloma (MM). The benefit of mobilization with Cy over filgrastim (granulocyte colony‐stimulating factor; G‐CSF) alone is unclear. Between 2000 and 2008, 167 patients with newly diagnosed MM underwent single ASCT after melphalan conditioning at our institution. Seventy‐three patients were mobilized with G‐CSF alone, and 94 patients with Cy plus G‐CSF (Cy+G‐CSF). We retrospectively analyzed Cy's impact on both toxicity and efficacy. Mobilization efficiency was augmented by Cy; a mean total of 12 versus 5.8 × 10 6 CD34+ cells/kg were collected from patients mobilized with Cy+G‐CSF versus G‐CSF, respectively, ( P < 0.01), over a mean of 1.6 versus 2.2 days of peripheral blood apheresis (p = 0.001). Mobilization‐related toxicity was also, however, augmented by Cy; 14% of Cy+G‐CSF patients were hospitalized because of complications versus none receiving G‐CSF ( P < 0.0001). Toxicity, including death, related to ASCT was similar between cohorts. Regarding long‐term outcomes, multivariate analysis revealed no difference for Cy+G‐CSF versus G‐CSF (hazard ratio 0.8 for event‐free survival [95% confidence interval CI 0.57–1.25] and 0.96 for overall survival [95% CI 0.61–1.54]). In summary, we show that mobilization with Cy increases toxicity without positively impacting long‐term outcomes in MM. Our findings place into question Cy's benefit as a routine component of stem cell mobilization regimens in MM. Randomized trials are needed to elucidate the risks and benefits of Cy more definitively. J. Clin. Apheresis 30:176–182, 2015. © 2014 Wiley Periodicals, Inc.